Efektivitas Perencanaan Pembelajaran IPS terhadap Kinerja Guru IPS Dalam Mengajar - Amini Amini; Amanda Salsabila; Yusril Amsari Rambe; Ihwani Ihwani; Anggi Shufiah Rahmah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This journal discusses social studies learning planning that can improve the performance of social studies teachers in teaching, the place where this scientific work was made is at SMP Negeri 1 Pagar Merbau. The purpose of this research is to see and describe the planning and implementation of IPS learning in class. This type of research is qualitative with a naturalistic approach. The source of the data from this study was interviews with social studies teachers at schools and students. The results of this study are the creation of lesson plans (RPP) that can improve teacher performance in teaching classes so that they can automatically increase students’ interest in learning. Because the good readiness of a teacher before teaching will have a positive impact on student learning itself. Keywords: Learning Planning, IPS Learning, IPS Teacher Performance